The development of information infrastructure and technological capabilities used to manage social care and address quality in primary care settings - Anthony M. Provenzano; Faiyaz Syed; Jodyn E. Platt; Gretchen A. Piatt; Mark S. Ackerman; Ayse Buyuktur; Michael S. Klinkman (BMC Health Services Research)
Abstract Background With new payment systems to prompt more sophisticated data activities, primary care practices are developing technological capabilities to manage patient care and information. One burgeoning capability is the collection of social determinants of health (SDOH) data and using that information to provide social care. This study describes the information infrastructure and technological capabilities developed by community health centers (CHCs) and examines the factors influencing SDOH data integration and management in primary care practice. It offers health care leaders insights and strategies to build capacity for managing social care and quality. Methods An observational design was used to examine the technological capabilities of CHCs in Michigan via a practice survey, and factors related to developing information infrastructure were qualitatively explored. The practice survey, semi-structured interviews, and national health center data were analyzed. Sociotechnical systems and organizational theories were used to develop the survey and interview guide. A sample of Michigan CHCs (n = 15) was recruited for the study. The practice survey was administered to CHC leaders, clinicians, and staff (n = 27). Semi-structured interviews (n = 25) were then conducted to explore infrastructural, organizational, and technological factors associated with managing social care and information. Results Michigan CHCs developed capabilities to exchange patient information with state and local partners. Data were typically shared with maternal and infant health (n = 5, 33.3%), mental health (n = 5, 33.3%), substance use (n = 6, 40%), domestic violence (n = 6, 40%), and food assistance (n = 6, 40%) providers, but CHCs did not develop the same capabilities with all social services examined. The interviews revealed that CHCs leveraged health care and government investments in information technology (IT) as a strategy to share data and address quality. The survey results revealed that CHCs developed the ability to use SDOH data to manage population health and provide value-based care. Conclusions IT used to manage social care and address quality is necessary but insufficient in primary care settings. The technological capabilities developed to integrate SDOH data into practice and exchange health information support critical infrastructure and learning opportunities to improve care, quality, and outcomes.